2016
DOI: 10.1021/acs.langmuir.6b02897
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Surface Chemistry of Transparent Butyl Rubber for Impermeable Stretchable Electronics

Abstract: Transparent butyl rubber is a new elastomer that has the potential to revolutionize stretchable electronics due to its intrinsically low gas permeability. Encapsulating organic electronic materials and devices with transparent butyl rubber protects them from problematic degradation due to oxygen and moisture, preventing premature device failure and enabling the fabrication of stretchable organic electronic devices with practical lifetimes. Here, we report a methodology to alter the surface chemistry of transpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…We deposited GPTMS on the T-IIR surface by using our previously reported method, whereby a plasma oxidation step initially produces a low density of oxidized functional groups on the surface. 24 Subsequently exposing this surface to silicon tetrachloride vapor in ambient conditions deposits a thin silicate film on the surface (T-IIR/SiO 2 ), which then supports the formation of the GPTMS layer. Bringing the APTES-modified PDMS membrane into conformal contact with the GPTMS-modified T-IIR surface enables the interfacial ring-opening reaction, adhering the PDMS membrane to the surface of T-IIR to yield the PDMS-T-IIR MINE structure, which we term MINE-30 to denote the PDMS membrane thickness ( Figure S2).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We deposited GPTMS on the T-IIR surface by using our previously reported method, whereby a plasma oxidation step initially produces a low density of oxidized functional groups on the surface. 24 Subsequently exposing this surface to silicon tetrachloride vapor in ambient conditions deposits a thin silicate film on the surface (T-IIR/SiO 2 ), which then supports the formation of the GPTMS layer. Bringing the APTES-modified PDMS membrane into conformal contact with the GPTMS-modified T-IIR surface enables the interfacial ring-opening reaction, adhering the PDMS membrane to the surface of T-IIR to yield the PDMS-T-IIR MINE structure, which we term MINE-30 to denote the PDMS membrane thickness ( Figure S2).…”
Section: Resultsmentioning
confidence: 98%
“…We have previously shown that T-IIR undergoes destructive bond scission reactions in air or oxygen plasma, producing a low density of oxidized functional groups on the surface. 24 Creating a hydrophilic T-IIR surface requires additional chemical treatment with silicon tetrachloride vapor, which deposits a thin, hydrophilic silicate film on the surface, similar to the surface formed by the simple one-step plasma oxidation of PDMS. 12 In the present paper, we further show that PVD of metals-the routine method used to fabricate stretchable conductors on PDMS-produces discontinuous metal films on the T-IIR surface that are inoperative as stretchable conductors.…”
Section: The Bigger Picturementioning
confidence: 99%
“…While oxygen must be eliminated to prevent quenching of triplet excitons, it may be possible to use oxygen barriers that are already commercially available, e.g. polyisobutylene, 134,135 or the barrier layers used in the commercial production of OPV cells.…”
Section: Discussionmentioning
confidence: 99%
“…44 Recently, butyl rubbers have been used as hermetic seals for stretchable electronics. 45,46 Despite its relatively low permeability, butyl rubber is still too permeable to prevent dehydration of hydrogels at the scale of a typical textile fiber; see Table 1.…”
Section: ■ Coat and Humectantmentioning
confidence: 99%